Mapear é preciso: arte urbana, relações de poder e o Festival Concreto na cidade de Fortaleza - Lemos, Aliria Aiara Duarte (2019)
In the city of Fortaleza, urban art, in their different expressions, presents promising scenarios and, at the same time, with many contrasts. If by a side the city coexists coexist with the absence of cultural policies in forgotten neighborhoods and "off" the map, by the other side I can see arises an urban art festival that directs the attention to a concentrated action on routes around the conventional spaces of art. Therefore I realize the need for more embracing cultural policies that make these neighborhoods visible, their stories, and memories so that they do not fall into oblivion. Seeing all spheres of social life are made of power relations and, ,in this study, by the microphysics of power and speech analysis concepts as references ( FOUCAULT, 1998,1996) I ask how these relations for the urban art performance in the Festival Concreto happens. By following the Festival process of preparation and realization, with cartography and ethnography inspirations, I present for the analysis the speeches and tensioned practices from the relations between art and politics and the concepts of disagreement and dissent (RANCIÈRE, 1996a, 1996b). At the process of the research, I realize a mapping exercise by locating visibility and abandonment places, independent artistic performance and by Festival Concreto and where public and private power are more present. With the contributions form Alexandre Barbalho and Antônio Albino Canelas (2007) which extend the notion of a multidisciplinary perspective culture area, I also consider aspects of how urban art is today being connected to cultural policies, state and private support, in Fortaleza. The reading of how neoliberalism works and the market logic, which tends to add various structures, as cultural and public policies, the art system and all other social areas. How this expand the analysis condition that involves the Festival Concrete‟s realization, as well other actions from artistic public and private institutions, pointing the relevance of studies and artistic propositions that question the logic of the market, crossing geographical boundaries and building new power relations that expand the dialogue between the city beyond the conventional spaces of the arts and the cultural and tourist routes.